Reliability of Upper Extremity Functional Performance Tests for the Non-overhead Athlete - Bryan L Riemann; George J Davies (North American Sports Medicine Institute, 2023)
# Background While there have been reliability studies conducted on several upper extremity functional performance tests (UEFPT), there are several complicating factors that inhibit the ability to draw definitive consensus about the reliability of the tests in both females and males. Having reliability estimates for UEFPT in the same cohort facilitates direct comparison of their relative and absolute reliability. # Purpose To establish the test-retest reliability of the closed kinetic chain upper extremity stability test (CKCUEST), seated medicine ball chest pass test (SMBCPT) and hands-release push-up test (HRPUT) in a cohort of males and females with a history of non-overhead sport participation. A secondary purpose was to examine the associations between the three UEFPT. # Study Design Test-retest reliability, single cohort study. # Methods Forty adults (20 females, 20 males) with a history of non-overhead sport participation completed three UEFPT during two data collection sessions three to seven days apart. Measures of systematic bias, absolute reliability and relative reliability were computed between the sessions. Additionally, correlational analyses were conducted between the three UEFPT. # Results Only the UECKCST (both sexes) demonstrated significant (p≤ 0.003) second session performance improvements. All three tests exhibited excellent relative reliability (intraclass correlational coefficients ≥ 0.823) and except for the HRPUT in males, coefficients of variation were all below 8.8%. Except for a significant relationship (r=.691, p=0.001) between the UECKCST and SMBCPT for the females there were no other associations between the three UEFPT. # Conclusion All three UEFPT demonstrated sufficient reliability. Thus, all three assessments can be used for serial assessments to progress a patient through rehabilitation as well as contribute to the criteria used in making return to sport decisions. # Level of Evidence 3